2004
DOI: 10.1248/bpb.27.634
|View full text |Cite
|
Sign up to set email alerts
|

Feitai Attenuates Bleomycin-Induced Pulmonary Fibrosis in Rats

Abstract: Pulmonary fibrosis is a common consequence of numerous pulmonary diseases. The current therapeutic approaches for this condition are unsatisfactory. Feitai, a composite formula consisting of several herbs, is used in China as a folk remedy for treating patients with pulmonary tuberculosis. In this study, we extensively investigate the effects and mechanisms of Feitai on bleomycin (BLM)-induced pulmonary fibrosis in rats. One hundred and twenty male Sprague-Dawley rats were randomly divided into four groups, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…These changes were a likely consequence of the severe morphological alterations occurring in the lung following bleomycin treatment, which manifested as a heterogeneous distribution of dense inflammatory cell infiltrate and accumulations of fibrous masses and bands in the lung parenchyma, coupled with thickening of the alveolar walls, all of which are observations consistent with previous reports [26,27,28]. Likewise, as with previous reports, bleomycin-treated C57BL/6 mice developed pulmonary oedema, deduced from the significant increase in wet lung weights following bleomycin treatment, compared to vehicle control mice [29,30]. Furthermore, albeit not a significant difference, the observed reduction in body weight of bleomycin-treated C57BL/6 mice was likely to be the outcome of the brisk inflammatory response occurring in the lung as previously reported [29,31,32,33,34,35].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These changes were a likely consequence of the severe morphological alterations occurring in the lung following bleomycin treatment, which manifested as a heterogeneous distribution of dense inflammatory cell infiltrate and accumulations of fibrous masses and bands in the lung parenchyma, coupled with thickening of the alveolar walls, all of which are observations consistent with previous reports [26,27,28]. Likewise, as with previous reports, bleomycin-treated C57BL/6 mice developed pulmonary oedema, deduced from the significant increase in wet lung weights following bleomycin treatment, compared to vehicle control mice [29,30]. Furthermore, albeit not a significant difference, the observed reduction in body weight of bleomycin-treated C57BL/6 mice was likely to be the outcome of the brisk inflammatory response occurring in the lung as previously reported [29,31,32,33,34,35].…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, as with previous reports, bleomycin-treated C57BL/6 mice developed pulmonary oedema, deduced from the significant increase in wet lung weights following bleomycin treatment, compared to vehicle control mice [29,30]. Furthermore, albeit not a significant difference, the observed reduction in body weight of bleomycin-treated C57BL/6 mice was likely to be the outcome of the brisk inflammatory response occurring in the lung as previously reported [29,31,32,33,34,35]. …”
Section: Discussionsupporting
confidence: 88%
“…The first line of therapy in clinic, specifically the use of corticosteroids like dexamethasone, the comparative drug in the present study, is based on its anti-inflammatory effects. Our previous study showed that treatment with Feitai at dose of 3 g/kg BW significantly decreased inflammatory response induced by BLM in the acute phase, as reflected by reducing BLM-induced increase in total and differential cell counts in BALF and myeloperoxidase activity in lung (Gong et al, 2004). Based on these results, we conclude that the anti-inflammatory effects of Feitai contribute to its protective effect against pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 57%
“…Rats were intratracheally injected with BLM (5 mg/kg BW, 2 ml/kg BW) or saline as described previously (Gong et al, 2004). The day of intratracheal injection with BLM or saline was designated day 0.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…One portion of each homogenate was centrifuged at 3000×g for 10 min at 4 °C, and the supernatant was used for the measurement of malondialdehyde concentration and ACE activity. The malondialdehyde concentration was determined by the thiobarbituric acid method as previously described [19] . ACE activity was analyzed, as previously described [20] , by measuring the hydrolysis of Hippuryl-L-histidyl-L-leucine ( Hip-His-Leu; Sigma, USA) substrate to histidyl-leucine (His-Leu), which fluoresces at an excitation wavelength of 365 nm and an emission wavelength of 495 nm.…”
Section: Methodsmentioning
confidence: 99%